2015
DOI: 10.1016/j.physio.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy clinical educators’ perceptions and experiences of clinical prediction rules

Abstract: Students are unlikely to be learning about CPRs on clinical placement, as few clinical educators use them. Clinical educators will require training in CPRs and assistance in teaching them if students are to better learn about implementing CPRs in physiotherapy clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The most common reasons for this were students not knowing enough about CPRs or not using them often enough (81%) and a perceived lack of use or knowledge about CPRs by clinical educators (80%). This is consistent with a recent survey of physiotherapy clinical educators [10], which found that a large proportion of educators knew little about CPRs and so were unlikely to be teaching them to students on clinical placement.…”
Section: Student Experience With Cprs On Clinical Placementsupporting
confidence: 90%
See 4 more Smart Citations
“…The most common reasons for this were students not knowing enough about CPRs or not using them often enough (81%) and a perceived lack of use or knowledge about CPRs by clinical educators (80%). This is consistent with a recent survey of physiotherapy clinical educators [10], which found that a large proportion of educators knew little about CPRs and so were unlikely to be teaching them to students on clinical placement.…”
Section: Student Experience With Cprs On Clinical Placementsupporting
confidence: 90%
“…Those students who had used them reported that they were learning little about CPRs from their clinical educators. The 27% of student users who reported they were 'sometimes' or 'always' learning about CPRs whilst on clinical placement (Figure 1) represent less than 6% of total respondents, and so most students are unlikely to be taught CPRs in the clinical setting, supporting the findings of our survey of physiotherapy clinical educators [10]. Arguably if students have such a poor understanding of CPRs or are using them inappropriately, it highlights the need for better education regarding EBP (including CPRs) in the classroom and in the clinic.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations